If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 = a + 18 Reorder the terms: -11 = 18 + a Solving -11 = 18 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. -11 + -1a = 18 + a + -1a Combine like terms: a + -1a = 0 -11 + -1a = 18 + 0 -11 + -1a = 18 Add '11' to each side of the equation. -11 + 11 + -1a = 18 + 11 Combine like terms: -11 + 11 = 0 0 + -1a = 18 + 11 -1a = 18 + 11 Combine like terms: 18 + 11 = 29 -1a = 29 Divide each side by '-1'. a = -29 Simplifying a = -29
| 2(x-3)+4=4x+22 | | 14x+25-11.5=100 | | 26x-7-14x+3=22x-5-10x+11 | | 1.42=log(x) | | 2(2z+2)-6=30 | | 9x-11-8x=3 | | 7x+4-9x=12-18x+16x-8 | | 4tan(x)+5=4 | | 5v-v=10+5 | | 9b+3=84 | | y=15-(-18) | | 5x-8x+25=2x+35 | | 4x^2-16x=116 | | x+7=3x-19 | | x-3+3x=309 | | -1*(-3)-2= | | -10-1x=2 | | .3(15-2y)-.2y=.5 | | 2y-4=19y+64 | | x^2-2mx+8m-15=0 | | y=ln(5x+8) | | -20+x=x+30 | | 76678x+2435x-2=2x | | 5x+3+6=53 | | 3x+1-4=16 | | (t+8)=(3t-7) | | -7-4n-4=-112 | | 5y-4+y+42=6y+50-4y | | (-1)-(-2)(-3)= | | y=-2x-24 | | 9+2n-6=9n+10-6n | | 4x^2+13x+5=0 |